Integração entre projetos na alvenaria estrutural - Buriol, Evandro Augusto (2003)
The use of structural masonry is growing in the state of Rio Grande do Sul. The interest for this system is related to the rationality of its constructive process ally to the expectation of construction with quality and less costs. A structural masonry project must have low plants, elevation of all walls and constructive details, besides the specifications and other documents that come along with the project. Thus, this work aims to identify the reasons why the constructive errors happen, even this system is based on modulation and rationalization, oriented by detailed projects. One questionary was elaborated to be applied during building site visits, with the purpose of identifying these errors. This questionary involves the project and execution phases, focusing on the interferences of installations, as the electrical and hydro-sanitary, during the constructive process. Having this information, a manner of integrating all the projects at the beginning of the work is aimed. The more common errors are described and some ways to avoid them are recommended. More attention is required for the technical standards related to the structural masonry and to the installations. As conclusions, it should have more information exchange among designers, and among designers and executers, providing the elaboration of integrated projects, which, associated with a better labour, warrants a more qualified and rationalized constructive process.